THE RELATIONSHIP BETWEEN INTERIOR DESIGN AND ARCHITECTURE - Idaura Fadhya Che Ibrahim; Syed Ahmad Iskandar Syed Ariffin; Alice Sabrina Ismail (Journal of Islamic, Social, Economics and Development, 2022)
Architecture and interior design have struggled with how and where they intersectas professions and as academic disciplines. Architects believe that the design of interior spacefalls under their jurisdiction; that the architect is qualified by education and experience todesign the interior and that they have always had this responsibility. At this time, theinformation stipulated on the knowledge areas and a set of skills published in the InteriorDesign Body of Knowledge is insufficient in providing clear guidance on the territories betweeninterior design and architecture. There is a discrepancy in the information understood by theperspectives of education and industry in the definition of the profession. The need for clarityon what differentiates these two professions is a critical issue to avoid confusion andmisrepresentation in professional roles and academic curricula structures. Henceforth, thisstudy attempts to discuss the determinants shared similarly between architecture and interiordesign profession. The qualitative method is employed through a comparative and contentanalysis. Published and unpublished documents was retrieved from main databases which wereScopus, Science Direct, Google Scholars, Google engine search and the key professionalassociations, to facilitate the comparison. Reviewing the documents reveals that eachprofession acquires different knowledge. The findings showed that interior designers are notarchitects and not taught, qualified, or checked as architects. Conversely, architects are noteducated, trained, or tested to be interior designers. The professions, on the other side, arecomplementary.